Food Security and Sustainable Developmental Goals:Relationships and Implications for Attainment - Oni , Isaac Oluwadamilare; Olajide , Oluwabunmi Bola; Olajide , Damilola Deborah (International Journal of Health, 2025)
Food security is a phenomenon that is of global public health interest. It is also integral ‎to the attainment of the 2030 target for the 17 Sustainable Development Goals (SDGs). ‎Food is a basic necessity of life and central to human existence. Food security is ‎relevant to the gross productivity at both the individual and national levels. The objectives of this review are to establish the connection between food security and 17 ‎SDGs, challenges to secured food systems as well as global trend for ‎food insecurity. A search for relevant articles published until November 2024 from ‎popular repositories was conducted. The key terms used for the search included words ‎and/or phrases related to food security, sustainable development goals, food insecurity‎, and challenges of food security. This review presents an overview of the continuous ‎increase in the rate of food insecurity, the challenges limiting the actualization of food ‎security, and the sheer connection between food security and other SDGs, as well as the ‎implications for the attainment of other SDGs. Due to the existing network between food ‎security and these SDGs, the application of one health concept would be crucial ‎to overcoming several challenges in public health. Multi-sector collaboration and ‎partnership would be important in reducing food insecurity to the barest minimum‎.